STUDY OF PROFILE OF ORGANOPHOSPHORUS POISONING CASES IN A TERTIARY CARE HOSPITAL, NORTH KARNATAKA, BIDAR, INDIA. - DR PADMANABHA T S,; DR KASHINATH GUMMA,; DR GAJANAN P KULKARNI, (International Journal of Pharma and Bio Sciences, 2014)
A retrospective analysis of Organophosphorus(OP) poisonoing cases admitted to emergency wards of BRIMS, Government Teaching Hospital, Bidar, Karnataka from July 2012 to Dec 2012 was done to study the profile of poisoning cases reported. Since Acute poisoning due to Organophosphorus compound is a common medical emergency and leads to morbidity and mortality in developing countries due easy accessibility and less cost of OP compounds in the market. Hence the present study is undertaken to know the poisoning pattern at BRIMS Teaching Hospital, Bidar. Objective of the study was to evaluate the pattern of OP poisoning and to study the socio-demographic profile of the same